KAJIAN EFISIENSI PERBANKAN SYARIAH DI INDONESIA (PENDEKATAN DATA ENVELOPMENT ANALYSIS) - H. Rahmat Hidayat (Universitas Trisakti, 2011)
The history of Islamic banks in Indonesia is started by establishment of Bank Muamalat Indonesia (BMI) as the first Islamic commercial bank in Indonesia that has been operated in Indonesia in 1992. Until December 2007, there are 31 banks: 3 Islamic commercial banks and 28 Islamic unit banks. Islamic commercial bank operates fiilly sharia system, while Islamic unit bank operates windows system. During 2003-2007, Islamic banks have been grown significantly include asset, deposit and financing. Each grows 53%, 56% and 55% per year. Islamic banks must improve thier efficiency in order to give profit to stakeholders, and survive againts conventional banks or other financial institutions. Nevertheles, until today the efficiency of Islamic banks in Indonesia is not known. This study to identify: the efficiency of Islamic banks in Indonesia (overall), the efficiency of individual Islamic bank, the difference efficiency of Islamic commercial bank and Islamic unit bank, and the most influence factor to the efficiency of Islamic banks in Indonesia. This study focused on the head office of Islamic banks. The study uses data quarterly from fist quarter 2003 until fouth quarter 2007, includes nine banks: three Islamic commercial banks and six Islamic banking units. This study uses non-pametric DEA model. The results of this study show the efficiency of Islamic banks in Indonesia is average 0.883, and the most efficient Islamic banks is bank 1 (from Islamic commercial bank). Furthermore, the result of study indicates that Islamic commercial bank (BUS) is more efficient than Islamic unit bank (UUS). Besides that, financing is the most influence factor to the efficiency of Islamic banks in Indonesia. As the basic implication of this study are: (i) stakeholders especially government and monetary authority must improve the efficiency of Islamic banks and support and establish more Islamic commercial bank; (ii) stakeholders must support and establish more Islamic commercial bank, includes spint off Islamic unit bank to be Islamic commercial bank; and (iii) Islamic banks must give more financing to improve their efficiency.Keywords: Efficiency, Islamic commercial bank, Islamic unit bank, DEA